EVALUASI DAN PERKEMBANGAN KEBUTUHAN AIR BERSIH DI KECAMATAN LILIALY-KABUPATEN BURU: Evaluation and Development of Clean Water Needs in Lilialy-Buru Regency - Andi Sudarman, Sjaid S. Fais Assagaf, Irmawati Mukadar (Uniqbu Journal of Exact Sciences, 2020)
This research is more focused on analyzing the projected population growth and the need for Clean Water for the next 10 (ten) years so that it can be systematically planned for the design of the Water and Clean Water infrastructure needs. In order to meet the projected population growth and the need for clean water, it must be known how the population is in accordance with the supply of clean water needed by the people of Lilialy Subdistrict. which will come. The location of this research is in Lilialy Subdistrict and is limited to the population projection whether it is in accordance with the provision of clean water needs needed by the community and to assess and plan for the needs of clean water for the next 10 years. Projection of Clean Water Needs both SPAM and Graphitation System is calculated based on domestic needs and the loss of water is there because Drinking Water and SPAM needs are influenced by population growth in Lilialy District in 2016 domestic and SPAM drinking water needs are 3.11 liters / sec and at in 2024 the need for domestic drinking water is 3.49 liters / second.